Modelling of carbon dioxide absorption in aqueous solutions of AMP and MDEA and their blends using Aspenplus - Aroua, M.K.; Haji-Sulaiman, M.Z.; Ramasamy, K. (Separation and Purification Technology, 2002)
In this paper the results of an experimental investigation on the solubility of CO2 in methyldiethanolamine (MDEA), a tertiary amine, and 2-amino-2-methyl-1-propanol (AMP), a primary sterically hindered amine as well as their mixtures are presented. It is shown that AMP CO2 uptake is higher as compared to that of MDEA. The addition of AMP to MDEA enhances the CO2 loading of the latter. The experimental data for single amines are used to generate the electrolyte NRTL model parameters that is available in the AspenPlus Software. The results have indicated that parameters generated using data obtained at limited operating conditions are able to accurately predict the CO2 solubilities at other conditions. Furthermore, the model is also able to estimate the CO2 loading in AMP-MDEA mixtures.